The A to E (ABCDE) Pit Crew Model: A Novel Approach to Team Based Care of Critical Patients in the Prehospital Setting - Ayanna Walker; Adam Oswald; Jessica Wanthal; Christine Van Dillen; Cherian Plamoottil; Parth Patel; Maria Tassone; Latha Ganti (Health Psychology Research)
# Background